Bridging Faith and Market: A Bibliometric Exploration of the Halal Hotel Landscape - Muhammad Zen Nasrudin Fajri; Abdul Latif; Abdul Latif Rizqon; Arie Rachmat Sunjoto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study explores how research on halal hotels has evolved, what themes have emerged over time, and where future scholarship should focus especially as the demand for faith-aligned hospitality continues to grow. Using a dataset of 139 documents retrieved from the Scopus database between 2009 and 2025, the study applies bibliometric analysis via Biblioshiny and VOSviewer to map publication trends, influential authors, institutions, and countries. Keyword co-occurrence analysis is used to identify thematic clusters. Content analysis of selected articles is then conducted to synthesize key research trends and challenges. The findings show that Halal hotel research is growing steadily, with Malaysia and Indonesia contributing the most. The field centers around seven key trends: certification and standardization, faith-driven traveler behavior, service quality, branding and digital engagement, internal ethical management, emerging technologies, and broader tourism integration. However, gaps remain, particularly around inconsistent standards, vague branding, and ethical questions surrounding tech use. To support future research, this study outlines 20 actionable questions tailored to the needs of practitioners. The findings provide useful direction for those designing, managing, or regulating halal hotel services, especially those aiming to bridge Islamic values with market realities.